'One blue'. Issue 1 (March 2017) - Foley, Ronan
This paper responds to Winder and Le Heron's (2017) article on the Blue Economy and starts by acknowledging their laudable attempt to critically examine the terminology and in particular its economic framing. Their articulation of how this can be extended to consider bioeconomic relations, ethics and politics and where geographers play a role in innovative forms of knowledge production is then critically examined. I suggest that the term blue needs to be examined more fully alongside the term economic and identify a range of complex palettes and forms that need to be considered. In addition, I propose that health in a range of forms, both human and non-human, might be fed into the mix to deepen their discussion of both value and ethics of care. Finally, the notion of 'one blue', following the example of 'one health', is tentatively suggested as a conceptual term to deepen their call for stronger aspects of therapeutic assemblage thinking to be fed into future ocean and marine management.